The Application of Al-Qardh Financing in the Sharia Financing Savings and Loans Cooperative Makmur Gemilang Sejahtera Magelang Indonesia (Approached with Fatwa DSN MUI No. 19/IV/2001) - Zulfatus Sa’diah; Mochammad Kharits Taufani (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Al-Qardh financing is one proof of the development of Islamic finance. One of these financing efforts is for the welfare of the community by providing assistance without compensation. This financing is not aimed at getting financial benefits but at expecting the blessing of Allah SWT. This research was held at KSPPS Makmur Gemilang Sejahtera Magelang. The data analysis method used is descriptive analysis method. Through this discussion, the researcher will describe the data that has been obtained through the results of observations, interviews or documentation that will be analyzed using the DSNMUI fatwa. The results showed that in the application of qardh financing carried out at KSPSS customers who want to finance there is an additional fee of 2.5% on each principal amount of financing for infaq / alms agreed upon at the beginning of the agreement agreement. So the implementation process is not completely perfect with the fatwa, because the 5th point "Al-Qardh customers can provide additional (voluntary donations to LKS as long as they are not promised in the contract)". According to the DSN-MUI fatwa, donations cannot be promised in the contract, even if it is infaq/almsgiving, because the addition can be categorized as Riba